Significant indicators in the assessment of environmental tourism carrying capacity (ETCC) : a case study at Royal Belum State Park, Perak Darul Ridzuan - Noorul Iffa binti Mohd Nayan (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2014)
Carrying capacity concept is viewed as a weak concept in tourism management and planning although the original theory was seen as a remarkable solution in controlling the impacts of tourism towards the environment. However, due to its complexity and vagueness in indicating attributes and criteria to govern the framework, this theory received big criticism among scholars. Hence, this study was carried out to evaluate the importance of indicators over another to produce a hierarchical structure of environmental tourism carrying capacity (ETCC) framework for Royal Belum State Park (RBSP). ETCC is a site-specific way of implementation, where the indicators should be developed to solve the issues occurring on the site rather than being generalized for all sites. The methodology applied in this study is through triangulation approach which involves a process of identifying relevant indicators via content analysis, indicator screening via questionnaire survey, determining appropriate stakeholders via stakeholder analysis and evaluating the significant indicators via structured interview. The data collected were then analysed by using analytic hierarchy process (AHP) method rooted in the multicriteria decision making (MCDM) process. MCDM creates, evaluates and implements strategic decision deals with the procedures of choosing, ranking and sorting. The AHP technique is chosen amongst other available methods because it is widely applied in MCDM domains and has the ability to unveil relative priorities through pairwise comparison. From the study, it has been discovered that biophysical environment dimension (0.369) is the most important against tourism facility management (0.361), social-cultural (0.167) and political-economics dimension (0.103). Likewise, the top four indicators representing the four dimensions are wildlife threatened species (0.186), tourist satisfaction level (0.259), policy and regulations by park manager (0.300) and community profits (0.528). Based on these findings, it can be concluded that prioritizing the indicators could enhance the efficiency of ETCC, particularly in the implementation stage, by engaging appropriate stakeholders to participate in the data collection. This study also proved the theory that ETCC is a tailor made framework that works according to the issues and problems encountered at a specific site.